'Emotional authoritarianism': state, education and the mobile working-class subjects. Issue 4 (3rd July 2020) - Pun, Ngai; Qiu, Jack
ABSTRACT: Examining emotions within the studies of mobilities, recent literature has highlighted that migration is an inherently uncertain process shaped by hopes and dreams, as well as feelings of fear and anxiety. More than an individual pursuit for economic advancement or cultural assimilation, we find that migration is also a political project that incessantly creates valuable working-class subjects; a project that often starts in vocational training school, a site generating multiple forms of mobility between learning and workspaces. In the context of China, this article explores the emotional reproduction of working-class subjects through schooling and internship experiences, students' sense of belonging to the nation-state, their aspirations and fears for the future. Developing the concept of 'emotional authoritarianism', it examines the ways in which working-class students were influenced by state-engineered nationalistic sentiments, and how it became a conflictual process of subject-making. Emotional governance is a peculiar political strategy that shapes the emotions of working-class students who are expected to serve the growth of the national economy and transnational capitalism. We discover that mixed emotions or 'emotions in conflict' are fundamental to the class reproduction of migrant agents, torn among different bodies and desires in 'learning to labour'.